Heart-Type Fatty Acid-Binding Protein Enables Rapid Risk Stratification in Patients with Pulmonary Embolism - Utz Richter; Marian Christoph; Anne-Kathrin Tausche; Alessandra Boscheri; Martin Langer; Karim Ibrahim; Michael Günther; Ruth H. Strasser; Carsten Wunderlich (Journal of Hypertension and Cardiology, 2013)
Introduction: Elevated serum troponin levels are a reliable indicator of right ventricular wall stress in patients with acute pulmonary artery embolism (PE). Raised troponin levels have been shown to predict adverse clinical outcome in these individuals. In this context it was our aim to determine the additional role of the heart-type fatty acid-binding protein (H-FABP) in patients with acute PE. Methods: 87 consecutive patients with confirmed PE were included in the present study. On arrival a qualitative H-FABP-test (positive cut-off 7ng/ml) and a detailed echocardiographic study were performed in all patients. These findings were related to both in hospital and 30 days mortality. Results: Of the included 87 patients, 17 had positive H-FABP-tests. Right ventricular function was severely deteriorated in 10 patients (59%) in the H-FABP-positive group but only in 2 patients (3%) of the H-FABP-negative group (p<0.005). 15/17 patients (88%) of the H-FABP-positive group needed inotropic support, of these, 14 (82%) died in hospital. Only one patient with a H-FABP-negative test (n= 70) needed vasoactive drugs, and none of these patients died (p<0.005). Conclusion: H-FABP showed a better correlation with in-hospital mortality and RV-function than troponin I. Our data show that H-FABP significantly correlates with in hospital and 30-day mortality in patients with PE. Furthermore, it is associated with impaired right ventricular function and showed better correlation with mortality in patients with PE as compared to Troponin I. Thus, it may be viewed as a novel and promising tool to optimise the management strategy in these patients.
Keywords: Acute pulmonary embolism